TINJAUAN ATAS PROSEDUR PEMBAYARAN UTANG USAHA PADA PT SARANA UTAMA ADIMANDIRI - Annisa Aulia, (2022)
The final project report aims to study and understand more deeply about procedures within the company, especially procedures for paying debts. This final report discusses the procedure for payment of trade payables at PT Sarana Utama Adimandiri where the debt is an obligation arising from the purchase of goods or the use of services on credit and this obligation must be paid in less than one year. This procedure starts from purchasing goods or using services for the company's operational activities, preparing documents to support the payment of trade payables, and carrying out the debt recording process until the payment of the trade payables occurs. This procedure also involves several related functions and documents needed to support the payment of trade payables. The process of recording accounts payable is done using the Odoo system. With this procedure, the payment process for accounts payable at PT Sarana Utama Adimandiri can be completed in a more structured manner in accordance with the provisions in the company.